Use of thioctic acid in complex treatment of acute alcoholic pancreatitis - M. S. Funygin (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
The results of treatment of 27 patients with confirmed. acute alcoholic pancreatitis are studied. It is shown that application of thioctic acid in a dose of 600 mg in a day allows to localize process and to turn it on an aseptic way.